Ambiguous pricing of Nepalese medicines - Shankar, PR; Subish, P; Mishra, P; Lalit, M (Journal of Institute of Medicine Nepal, 2007)
Background: The National Drug Policy of Nepal aims to make the country self-reliant in drug production. Nepal follows a competitive market system where both domestic and foreign manufacturers compete. Previous studies had shown ambiguities in drug pricing. Recent studies are lacking. Hence the present study was carried out to obtain information on the price variation between Nepalese brands for different drugs. Methods: The prices of drugs listed in the December 2005 issue of Nepal Drug Review were analysed. The following formula was used for calculation. Percentage price variation = Price of most expensive brand – Price of least expensive brand x 100 Price of least expensive brand The drugs were grouped together into various therapeutic categories and for each category, the mean number of brands and the mean percentage price variation was calculated. Results: A total of 79 drugs and 537 brands were analysed. Thirty-five drugs which were being manufactured by a single manufacturer were listed but were not analysed. The maximum price variation was shown by the group of anthelminthics followed by antihistamines and antiemetics. Among the individual drugs, fexofenadine and albendazole showed the maximum variation. Three of the drug groups showed more than 50% variation. However, ten individual drugs showed more than 50% variation. Conclusion: Variations were observed in the prices of different brands of the same drug being manufactured by different Nepalese companies. Prescribers and patients should be educated about drug prices. Further studies are required. Key words: National Drug Policy, Nepal Drug Review, Ambiguous pricing The full text of this paper is available at Journal of Institute of Medicine website